Evaluasi Model Pembelajaran Discovery Learning Berbasis Penilaian Diri Dalam Meningkatkan Prestasi Belajar Siswa Di MTs Agung Alim Blado Pada Mata Pelajaran Al-Quran Hadits - Asari, Asari; Muslih, Moh.; soebari, Titien Soewastiningsih (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to describe the evaluation of the Discovery Learning learning model in improving student learning outcomes in the Al-Quran Hadith subject, in this research using the classroom action research method or PTK. Observations were carried out to determine the learning process using the Discovery Learning model, student learning motivation, and student learning outcomes. The research results show that the learning process with Discovery Learning includes asking questions, formulating hypotheses, designing and making observations, collecting data, analyzing data, and making conclusions. There were improvements in implementation from cycle 1 to cycle 2. Student motivation increased from the initial conditions to the first cycle and the second cycle. The percentage of students with low motivation decreased from 40% (initial condition) to 17.90% (cycle 1) and 0% (cycle 2). Motivation is decreasing from 50% (initial condition) to 42.90% (first cycle) and 13.58% (second cycle). High motivation increased from 10% (initial condition) to 39.20% (first cycle) and 86.31% (second cycle). Student learning outcomes also increased. The percentage of students who had not yet completed decreased from 50% (first cycle) to 8.33% (second cycle). Students who completed and exceeded the KKM increased from 50% (cycle 1) to 91.67% (cycle 2). The indicator of the success of this classroom action research is the percentage of students completing at least 80%, which has been achieved at 91.67%. So, this PTK was declared successful.